Cup-to-disc ratio measured clinically and via OCT in pediatric patients being monitored as glaucoma suspects for suspicious optic discs - Caroline Maria Zimmermann; Nur Cardakli; Courtney Lynn Kraus (Frontiers in Ophthalmology)
PurposeCompare cup-to-disc ratio (CDR) measured by clinical assessment and optical coherence tomography (OCT) in pediatric eyes being monitored as glaucoma suspects for suspicious optic disc appearance.DesignRetrospective cross-sectional study.MethodsAn institutional study following 221 eyes from 122 unique pediatric glaucoma suspects being monitored due to increased or asymmetric appearance of CDR. Ophthalmologic findings, including visual acuity, intraocular pressure, CDR measured by clinical assessment, average retinal nerve fiber layer thickness, and average CDR measured by OCT, were recorded for each participant’s initial and final examinations. CDRs measured clinically and by OCT were compared at both initial and final presentations.ResultsAverage age at presentation was 9.0 years old (95% CI: 8.0-9.9), and mean length of follow-up was 5.0 years (95% CI: 5.4-4.5). At initial presentation, 53 eyes had CDRs recorded by both clinical assessment and OCT, and at final presentation, 93 eyes had CDRs measured by both modalities. CDR measured by OCT was significantly larger than CDR measured clinically on initial and final presentation (p=0.002, p<0.001).ConclusionsMeasurements of CDR by clinician assessment were significantly smaller than measurements obtained via OCT imaging. However, the average difference between CDR measured clinically and by OCT was <0.1. Thus, OCT may be a suitable way to measure CDR in pediatric glaucoma suspects, especially when clinical exam proves difficult. Further research is needed to assess CDR in glaucoma suspects using OCT longitudinally and in the context of other optic disc measurements, such as disc area.